Reinforced modified polyethylene material and application thereof in pump head
By introducing modified fillers into polyethylene materials, a strong interface interaction is formed, the problem of insufficient mechanical properties of pure polyethylene materials is solved, and the impact and heat resistance of the material is significantly improved, and it is suitable for applications such as pump heads.
Patent Information
- Application Number
- CN202411919521.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
AI Technical Summary
The mechanical properties of pure polyethylene materials are relatively average, especially the impact strength is weak, which limits their use in pump head applications.
Reinforced modified polyethylene materials are used to form a powerful interface interaction with the polyethylene molecular chain through specially made modified fillers, improving the overall mechanical properties of the material.
The impact resistance and heat deformation resistance of enhanced modified polyethylene materials are significantly improved, making them more suitable for use in parts such as pump heads.
Smart Images

Figure CN119591962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene materials, in particular to a reinforced modified polyethylene material and application thereof in a pump head. Background Art
[0002] Polyethylene has excellent chemical stability and is resistant to corrosion by most acids and alkalis (not resistant to oxidizing acids), which makes it perform well in handling various chemical media.
[0003] Polyethylene has excellent low-temperature resistance, with the lowest operating temperature reaching -100~-70℃, and can maintain good mechanical properties even in cold environments.
[0004] Polyethylene is a non-toxic and odorless material that meets food and pharmaceutical grade hygiene requirements and is suitable for situations where extremely high requirements are placed on the safety of the transmission medium.
[0005] Polyethylene is easy to process and can be processed into various shapes and structures through blow molding, extrusion, injection molding and other methods, which is convenient for the manufacture and customization of pump heads.
[0006] Because polyethylene has good chemical stability and can resist corrosion from a variety of chemical media, it is particularly suitable for pump heads that transport corrosive liquids.
[0007] However, the mechanical properties of pure polyethylene materials are relatively general, especially the impact strength is relatively weak, resulting in certain limitations in its application in pump heads. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a reinforced modified polyethylene material and application thereof in a pump head.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A reinforced modified polyethylene material, characterized in that it comprises the following components in parts by weight: 60-68 parts of polyethylene resin, 15-20 parts of modified filler, 6-8 parts of plasticizer, 1-2 parts of polyhydroxyalkanoate, 2-3 parts of carbon nanotubes, 1-1.5 parts of stearate, 2-3 parts of magnesium hydroxide powder, 0.5-0.8 parts of titanate coupling agent, 1-2 parts of calcium carbonate whisker, and 5-7 parts of hydrogenated styrene-butadiene-styrene block copolymer.
[0011] As a further technical solution, the modified filler preparation method comprises the following steps:
[0012] (1) First, an unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is performed in a furnace to obtain a preliminary calcined product;
[0013] (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under the protection of an inert atmosphere, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product;
[0014] (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion;
[0015] (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C and kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.5. The mixture is reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler.
[0016] As a further technical solution, the preliminary calcination temperature in step (1) is 450° C. and the time is 2 hours.
[0017] As a further technical solution, the mass ratio of the preliminary calcined product, nano-silicon dioxide and potassium hydroxide powder in step (2) is 10:3-4:12;
[0018] The inert atmosphere is nitrogen.
[0019] As a further technical solution, the mass ratio of the secondary calcined product and deionized water in step (3) is 1:10;
[0020] The ultrasonic dispersion frequency was 40 kHz.
[0021] As a further technical solution, the mixing ratio of the dispersion, aluminum chloride and zinc chloride in step (4) is 100mL:4g:6g;
[0022] The mass fraction of the ammonia water is 25%;
[0023] The high-speed centrifugal rotation speed is 6500r / min.
[0024] As a further technical solution, the dioctyl terephthalate and dioctyl adipate are mixed;
[0025] The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:1.
[0026] As a further technical solution, the stearate is calcium stearate.
[0027] As a further technical solution, the number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190°C and under a load of 2.16 kg is 38 g / 10 min.
[0028] A reinforced modified polyethylene material is used for the pump head.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The reinforced modified polyethylene material prepared by the present invention has greatly improved performance, mainly in that its mechanical properties, especially the impact resistance, are significantly improved, so that it can be better applied in the field of pump heads.
[0031] The present invention adopts a specially prepared modified filler with an extremely high specific surface area, which can form a strong interface interaction with the polyethylene molecular chain. The enhanced interface bonding force enables the prepared reinforced modified polyethylene material to more effectively transfer stress when subjected to force, thereby greatly improving the overall mechanical properties of the reinforced modified polyethylene material, including tensile properties and impact properties.
[0032] When external force acts on the reinforced modified polyethylene material, the modified filler particles, as stress concentration points, can effectively disperse and absorb the impact energy, thereby effectively preventing the expansion of cracks, thereby improving the impact resistance of the reinforced modified polyethylene material.
[0033] The present invention further improves the various components and dosages of the material, thereby significantly improving the heat deformation resistance of the reinforced modified polyethylene material in a high temperature environment. Since pure polyethylene is easy to soften and deform, this will limit its application in the field of pump heads. Therefore, the present invention has made significant improvements in this performance.
[0034] By introducing a certain amount of magnesium hydroxide fraction, the flame retardancy of the reinforced modified polyethylene material can be effectively improved. The improvement of the flame retardancy can indirectly protect the reinforced modified polyethylene material from damage by external factors such as flames, thereby enhancing the overall durability and impact resistance of the modified polyethylene material to a certain extent, which is especially important for components such as pump heads that require high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 Statistical chart of bending modulus of each test group. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The following are specific embodiments:
[0039] Example 1
[0040] A reinforced modified polyethylene material, characterized in that it comprises the following components in parts by weight: 60 parts of polyethylene resin, 15 parts of modified filler, 6 parts of plasticizer, 1 part of polyhydroxyalkanoate, 2 parts of carbon nanotubes, 1 part of stearate, 2 parts of magnesium hydroxide powder, 0.5 parts of titanate coupling agent, 1 part of calcium carbonate whisker, and 5 parts of hydrogenated styrene-butadiene-styrene block copolymer.
[0041] A mixture of dioctyl terephthalate and dioctyl adipate;
[0042] The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:1.
[0043] The stearate is calcium stearate.
[0044] The number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190°C and under a load of 2.16 kg is 38 g / 10 min.
[0045] The modified filler preparation method comprises the following steps:
[0046] (1) First, unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is carried out in a furnace to obtain a preliminary calcination product; the preliminary calcination temperature is 450° C. and the time is 2 hours.
[0047] (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under inert atmosphere protection, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product; the mass ratio of the primary calcined product, nano-silicon dioxide and potassium hydroxide powder is 10:3:12;
[0048] The inert atmosphere is nitrogen.
[0049] (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion; the mass ratio of the secondary calcined product to the deionized water is 1:10;
[0050] The ultrasonic dispersion frequency was 40 kHz.
[0051] (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C, kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.5, reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler; the mixing ratio of the dispersion, aluminum chloride, and zinc chloride is 100 mL: 4 g: 6 g;
[0052] The mass fraction of the ammonia water is 25%;
[0053] The high-speed centrifugal rotation speed is 6500r / min.
[0054] Example 2
[0055] A reinforced modified polyethylene material, characterized in that it comprises the following components in parts by weight: 62 parts of polyethylene resin, 16 parts of modified filler, 6.5 parts of plasticizer, 1.2 parts of polyhydroxyalkanoate, 2.5 parts of carbon nanotubes, 1.2 parts of stearate, 2.2 parts of magnesium hydroxide powder, 0.6 parts of titanate coupling agent, 1.2 parts of calcium carbonate whisker, and 5.5 parts of hydrogenated styrene-butadiene-styrene block copolymer.
[0056] A mixture of dioctyl terephthalate and dioctyl adipate;
[0057] The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:1.
[0058] The stearate is calcium stearate.
[0059] The number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190°C and under a load of 2.16 kg is 38 g / 10 min.
[0060] The modified filler preparation method comprises the following steps:
[0061] (1) First, unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is carried out in a furnace to obtain a preliminary calcination product; the preliminary calcination temperature is 450° C. and the time is 2 hours.
[0062] (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under the protection of an inert atmosphere, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product; the mass ratio of the primary calcined product, nano-silicon dioxide, and potassium hydroxide powder is 10:3.2:12;
[0063] The inert atmosphere is nitrogen.
[0064] (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion; the mass ratio of the secondary calcined product to the deionized water is 1:10;
[0065] The ultrasonic dispersion frequency was 40 kHz.
[0066] (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C, kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.5, reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler; the mixing ratio of the dispersion, aluminum chloride, and zinc chloride is 100 mL: 4 g: 6 g;
[0067] The mass fraction of the ammonia water is 25%;
[0068] The high-speed centrifugal rotation speed is 6500r / min.
[0069] Example 3
[0070] A reinforced modified polyethylene material, characterized in that it comprises the following components in parts by weight: 65 parts of polyethylene resin, 18 parts of modified filler, 7 parts of plasticizer, 2 parts of polyhydroxyalkanoate, 2 parts of carbon nanotubes, 1 part of stearate, 3 parts of magnesium hydroxide powder, 0.7 parts of titanate coupling agent, 2 parts of calcium carbonate whisker, and 6 parts of hydrogenated styrene-butadiene-styrene block copolymer.
[0071] A mixture of dioctyl terephthalate and dioctyl adipate;
[0072] The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:1.
[0073] The stearate is calcium stearate.
[0074] The number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190°C and under a load of 2.16 kg is 38 g / 10 min.
[0075] The modified filler preparation method comprises the following steps:
[0076] (1) First, unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is carried out in a furnace to obtain a preliminary calcination product; the preliminary calcination temperature is 450° C. and the time is 2 hours.
[0077] (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under inert atmosphere protection, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product; the mass ratio of the primary calcined product, nano-silicon dioxide and potassium hydroxide powder is 10:3.5:12;
[0078] The inert atmosphere is nitrogen.
[0079] (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion; the mass ratio of the secondary calcined product to the deionized water is 1:10;
[0080] The ultrasonic dispersion frequency was 40 kHz.
[0081] (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C, kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.5, reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler; the mixing ratio of the dispersion, aluminum chloride, and zinc chloride is 100 mL: 4 g: 6 g;
[0082] The mass fraction of the ammonia water is 25%;
[0083] The high-speed centrifugal rotation speed is 6500r / min.
[0084] Example 4
[0085] A reinforced modified polyethylene material, characterized in that it comprises the following components in parts by weight: 68 parts of polyethylene resin, 20 parts of modified filler, 8 parts of plasticizer, 2 parts of polyhydroxyalkanoate, 3 parts of carbon nanotubes, 1.5 parts of stearate, 3 parts of magnesium hydroxide powder, 0.8 parts of titanate coupling agent, 2 parts of calcium carbonate whisker, and 7 parts of hydrogenated styrene-butadiene-styrene block copolymer.
[0086] A mixture of dioctyl terephthalate and dioctyl adipate;
[0087] The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:1.
[0088] The stearate is calcium stearate.
[0089] The number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190°C and under a load of 2.16 kg is 38 g / 10 min.
[0090] The modified filler preparation method comprises the following steps:
[0091] (1) First, unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is carried out in a furnace to obtain a preliminary calcination product; the preliminary calcination temperature is 450° C. and the time is 2 hours.
[0092] (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under inert atmosphere protection, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product; the mass ratio of the primary calcined product, nano-silicon dioxide and potassium hydroxide powder is 10:4:12;
[0093] The inert atmosphere is nitrogen.
[0094] (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion; the mass ratio of the secondary calcined product to the deionized water is 1:10;
[0095] The ultrasonic dispersion frequency was 40 kHz.
[0096] (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C, kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.5, reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler; the mixing ratio of the dispersion, aluminum chloride, and zinc chloride is 100 mL: 4 g: 6 g;
[0097] The mass fraction of the ammonia water is 25%;
[0098] The high-speed centrifugal rotation speed is 6500r / min.
[0099] Comparative Example 1: This comparative example is basically the same as Example 1, except that the modified filler is replaced by nano-silicon dioxide.
[0100] Comparative Example 2: This comparative example is basically the same as Example 1, except that the modified filler is replaced by nano-alumina.
[0101] Comparative Example 3: This comparative example is substantially the same as Example 1, except that no hydrogenated styrene-butadiene-styrene block copolymer is added.
[0102] test:
[0103] The melt index of the materials of the embodiment and the comparative example was tested and compared, and the test was carried out according to ASTM D1238;
[0104] Table 1
[0105] Melt index g / 10min Example 1 53.6 Example 2 52.3 Example 3 52.0 Example 4 53.5 Comparative Example 1 52.8 Comparative Example 2 52.2 Comparative Example 3 49.4
[0106] It can be seen from Table 1 that the melt index of the material of the present invention is significantly improved. By improving the melt index of the material, the processing performance of the material can be significantly improved.
[0107] The bending modulus of the samples of the embodiment and the comparative example was tested according to ASTM D638;
[0108] Table 2
[0109] Flexural modulus MPa Example 1 204.3 Example 2 211.6 Example 3 206.1 Example 4 210.8 Comparative Example 1 165.3 Comparative Example 2 170.2 Comparative Example 3 188.5
[0110] It can be seen from Table 2 that the modified polyethylene material prepared by the present invention has a higher flexural modulus.
[0111] The notched Izod impact strength of the example and comparative example materials was tested according to ASTM D256.
[0112] Table 3
[0113] <![CDATA[Izod impact strength of cantilever beam kJ / m 2 > Example 1 125.4 Example 2 122.8 Example 3 123.9 Example 4 124.2 Comparative Example 1 101.7 Comparative Example 2 97.5 Comparative Example 3 110.4
[0114] It can be seen from Table 3 that the impact properties of the modified polyethylene material prepared by the present invention are greatly improved.
[0115] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A reinforced modified polyethylene material, characterized in that: By weight The invention comprises the following ingredients: 60-68 parts of polyethylene resin, 15-20 parts of modified filler, 6-8 parts of plasticizer, 1-2 parts of polyhydroxyalkanoate, 2-3 parts of carbon nanotube, 1-1.5 parts of stearate, 2-3 parts of magnesium hydroxide powder, 0.5-0.8 parts of titanate coupling agent, 1-2 parts of calcium carbonate whisker and 5-7 parts of hydrogenated styrene-butadiene-styrene block copolymer.
2. A reinforced modified polyethylene material according to claim 1, characterized in that: The modified filler preparation method comprises the following steps: (1) First, an unsaturated polyester resin is added into a crucible, and then a preliminary calcination treatment is performed in a furnace to obtain a preliminary calcined product; (2) the primary calcined product obtained above is mixed evenly with nano-silicon dioxide and potassium hydroxide powder, and then heated to 720° C. in a tube furnace under the protection of an inert atmosphere, kept warm for 3 hours, and cooled to room temperature to obtain a secondary calcined product; (3) adding the secondary calcined product obtained above into deionized water, and then performing ultrasonic dispersion treatment for 20 minutes to obtain a dispersion; (4) Aluminum chloride and zinc chloride are added to the dispersion, stirred and mixed for 30 minutes, then heated to 80°C and kept warm for 10 minutes, and then ammonia water is added dropwise to adjust the pH of the system to 10.
5. The mixture is reacted at a constant temperature for 4 hours, cooled to room temperature, centrifuged at high speed for 15 minutes, filtered, washed to neutrality, and dried at 60°C for 12 hours to obtain a modified filler.
3. A reinforced modified polyethylene material according to claim 2, characterized in that: The preliminary calcination temperature in step (1) is 450° C. and the time is 2 hours.
4. The reinforced modified polyethylene material according to claim 2, characterized in that: The mass ratio of the preliminary calcined product, nano silicon dioxide and potassium hydroxide powder in step (2) is 10:3-4:12; The inert atmosphere is nitrogen.
5. The reinforced modified polyethylene material according to claim 2, characterized in that: The mass ratio of the secondary calcined product and deionized water in step (3) is 1:10; The ultrasonic dispersion frequency was 40 kHz.
6. The reinforced modified polyethylene material according to claim 2, characterized in that: The mixing ratio of the dispersion, aluminum chloride and zinc chloride in step (4) is 100 mL: 4 g: 6 g; The mass fraction of the ammonia water is 25%; The high-speed centrifugal rotation speed is 6500r / min.
7. The reinforced modified polyethylene material according to claim 1, characterized in that: The dioctyl terephthalate and dioctyl adipate are mixed; The mixing mass ratio of dioctyl terephthalate to dioctyl adipate is 2:
1.
8. The reinforced modified polyethylene material according to claim 1, characterized in that: The stearate is calcium stearate.
9. The reinforced modified polyethylene material according to claim 1, characterized in that: The number average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer is 120,000; the degree of hydrogenation of the aromatic unsaturated bonds in the structural units provided by styrene is 1.5 mol%, and the melt flow rate of the hydrogenated styrene-butadiene-styrene block copolymer at 190° C. and under a load of 2.16 kg is 38 g / 10 min.
10. The reinforced modified polyethylene material according to claim 1 is applied to a pump head.